Ubiquitous Learning Experience using VR in Electronic Science Education - Rajassekharan, Dinesh; B., Vivekanandam (Journal of Trends in Computer Science and Smart Technology, 2024)
In this technology-driven society, designing, prototyping and miniaturization of electronic systems pose major challenges, which in turn makes the electronic science education more essential. The objective of electronic science education is to increase students’ awareness to gain more technical proficiency to understand the miniaturized electronic system design and troubleshoot electronic systems. The evolution of electronic science with advanced technological achievements also faces contemporary challenges that virtual reality technologies are well-positioned to address. Virtual reality in electronic science education enhances learning by providing immersive and interactive experiences. It allows students to explore complex concepts, simulate experiments, and engage in hands-on activities, fostering a deeper understanding of electronic science principles. VR can create a dynamic and engaging learning environment, making abstract concepts more tangible and promoting experiential learning in a virtual space. This research study aims to encourage the active students’ participation in learning about the traditional and modern practices involved in electronics systems analysis while experiencing the immersive interaction related to various real-time conditions and applications.